BK polyomavirus in Iranian patients with papillary thyroid cancer: Is it a major future challenge?. Issue 12 (10th August 2022) - Tarharoudi, Rahil; Sari, Soyar; Sakhaee, Fatemeh; Vaziri, Farzam; Rahimi Jamnani, Fatemeh; Siadat, Seyed Davar; Fateh, Abolfazl
Abstract: BK polyomavirus (BKPyV) is a well‐known cause of nephropathy in renal transplant recipients. It has recently received much attention from researchers as a major predisposing factor for various cancers. This study aimed to investigate how BKPyV affected the advancement of papillary thyroid carcinoma (PTC). A total of 1057 samples were tested for BKPyV DNA and RNA, comprising 645 paraffin‐embedded PTC biopsy samples (PEBS), 412 fresh biopsy samples (FBS), and 1057 adjacent noncancerous samples. The BKPyV DNA was found in 511 (48.3%) of the specimens, including 347 (84.2%) FBS and 164 (25.4%) PEBS. The mean BKPyV copy number was significantly lower in patients with PEBS (0.5 × 10 −4  ± 0.1 × 10 −4  copies/cell) than in FBS (1.3 × 10 −1  ± 0.2 × 10 −1  copies/cell) and non‐PTC normal samples (0.3 × 10 −5  ± 0.04 × 10 −5  copies/cell). The PEBS had lower LT ‐Ag RNA expression than FBS, and no VP1 gene transcript expression was detected. In conclusion, although our findings indicated the presence of BKPyV in some Iranian PTC patients, more research is needed to corroborate these findings.